The Arthur of the Low Countries - Besamusca, Bart,Brandsma, Frank (University of Wales Press, 2021)
This book provides a comprehensive and informed survey of Arthurian literature in Dutch, aimed at readers who want to learn about the Arthurian tradition as it took shape in a language and culture with which they are not yet familiar.
Description based on publisher supplied metadata and other sources
Keywords: Aufsatzsammlung; Electronic books; Artus; Mittelniederländisch; Artusepik; Epic poetry; Dutch-History and criticism; Dutch poetry-To 1500-History and criticism